10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Objectives The global mpox outbreak that began in 2020 was declared a public health emergency of international concern in 2024. However, there is limited scientific evidence regarding the use of salivary and/or oropharyngeal swab samples to detect the virus. In this review, we systematically examined existing literature to evaluate the potential of saliva and/or oropharyngeal swab samples as screening tools for mpox detection. Methods The final analysis included 15 articles comprising 2,610 participants, including mpox-infected individuals (polymerase chain reaction confirmed) whose saliva and/or oropharyngeal samples (OPSs) tested positive for the virus. After a quality assessment, a random-effects model with logit transformation was used to pool the positivity rates. Results The pooled positivity rate of mpox virus DNA was 76.7% (95% confidence interval [CI], 27.9%-96.6%) in saliva and 69.7% (95% CI, 40.1%-88.8%) in OPSs. The high heterogeneity between the studies (I 2 = 99.5%) for both specimen types was addressed through sensitivity analyses. The median shedding durations were 19 and 21 d for saliva and OPSs, respectively. Conclusions The high positivity rates and sustained shedding in saliva and OPSs indicate that these methods can serve as noninvasive, adjunct, early-phase alternatives for rapid mpox detection, supporting enhanced surveillance, outbreak monitoring, and global public health preparedness.Knowledge Transfer Statement:The findings of this systematic review are directly relevant to clinicians, dental surgeons, and infection control specialists in understanding the diagnostic value of saliva and oropharyngeal samples for mpox. This knowledge can aid in screening, infection control, and patient management within health care settings.